Exploring Course Design Essentials as a Strategy for Effective Teaching and Learning in Developing Countries - David Francis Olebo; Tukur Muhammad; Michael Ben Okon; Ikwueze Stella Nneka; Happy James Burolerro; Jean Pierre Shumbusho (PT FORMOSA CENDEKIA GLOBAL, 2024)
Course design plays a pivotal role in shaping effective teaching and learning experiences. In developed countries, educational quality often surpasses developing nations; however, disparities in learning outcomes persist, particularly among students from lower socio-economic backgrounds. This study aimed to provide educators a comprehensive understanding of course design to bridge the gap. The benefits and challenges associated with each course design framework should be put into consideration while designing the course for learners by educators to enhance their teaching practices effectively. Recommendations Educators should prioritize clear learning objectives, embrace flexibility, adaptation, promote inclusive design, continuously evaluate and improve course designs. Finally, hybrid approaches recommended to leverage the strengths of other course design types